3x-4=2x-10

Simple and best practice solution for 3x-4=2x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4=2x-10 equation:


Simplifying
3x + -4 = 2x + -10

Reorder the terms:
-4 + 3x = 2x + -10

Reorder the terms:
-4 + 3x = -10 + 2x

Solving
-4 + 3x = -10 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-4 + 3x + -2x = -10 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-4 + 1x = -10 + 2x + -2x

Combine like terms: 2x + -2x = 0
-4 + 1x = -10 + 0
-4 + 1x = -10

Add '4' to each side of the equation.
-4 + 4 + 1x = -10 + 4

Combine like terms: -4 + 4 = 0
0 + 1x = -10 + 4
1x = -10 + 4

Combine like terms: -10 + 4 = -6
1x = -6

Divide each side by '1'.
x = -6

Simplifying
x = -6

 

See similar equations:

| 15x+6=10x+21 | | 9x+26+7x-17=2x+(-3x)+5x | | 7y-6y-10=13 | | -q-11=2q+4 | | 4t+9=-8t-13 | | 22p+11=4p-7 | | 17-9y=-3+16y | | 15m+22=7m+18 | | 3x+17=14+3x | | 3x+12-4x-12=11 | | 7(h+3)=6(h-3) | | -(5a+6)=2(3a+8) | | -2(2f-4)=-4(-f+2) | | 3w-6+2w=-2+w | | -8x-(3x+6)=4-x | | 14+3n=8n-3(n-4) | | 4(3m+4)=2(6m+8) | | -(3z+4)=6z-3(3z+2) | | 5x+2x-3=-3x+10 | | -2(j-3)=-2j+6 | | 6.8-4.2b=5.6b-3 | | -2(5.25+6.2x)=4(-3.1x+2.68) | | 0.5t+0.25(t+16)=4+0.75t | | 6x-5=44 | | 10x-45=155 | | -6(-p+8)=-6p+12 | | 9x+8=3x+62 | | 6x+7=2x+43 | | 6x+5=-5+2x+22 | | 0.50x+0.05(160)=0.25(108) | | 10(n+8)=2(40+5n) | | 3x-7=3(x-4) | | 7(7x-9)-5=49x-68 | | 8y+3(y-5)=5(y+2)-2 | | 3x+9=30 | | 7y+4(y-6)=5(y+2)-3 | | 11m=4 | | 2(2n-1)=(7n+2)+6 | | -36=4x-9 | | 3(x+2)+3=5x-2(-5+x) | | 0.12-0.01(x+2)=-0.02(4-x) | | 2-6(28x)=3x-76 | | 2+-6(28x)=2+-6(28x)-763x+-76 | | 2+-6(28x)=2+-6(28x)+763x+-76 | | 2+-6(28x)=2+-6(28x)+763x+76 | | 4-5y=19 | | .6k-.3=.5k+.4 | | 2.5+5.04m=8.5-.06m | | 2a-1=4(a+1)+7a+5 | | 3(k-2)-6=4k-(3k-1) | | 4(k+2)=k | | 14x-13j+18x= | | 3x+2y=11 | | 8+6x=50 | | 20-3x=-6 | | 1(2x+1)=27 | | 2(4x+7)=x-56 | | 5x+1=2x+15 | | 7x-18=45 | | 11x+6=8x+21 | | 12x-14=8x+2 | | x+42=15 | | 3x+30=12x-69 | | 2(x+7)=6x-10 | | 2x-2=12x-122 |